SCREENING OF SOYBEAN GERMPLASM COLLECTION RESISTANCE TO RUST DISEASE (Phakopsora pachyrhizi) - -, Sumartini (Proceeding of International Congress, 2014)
Rust disease is an important disease on soybean, it was widely distributed in almost all soybeanproducing countries, the yield losses can be reach 85 %. One of the control measured is planting theresistant varieties. Resistant gens of one character can be obtained from the germplasm collection. Thestudy aiar to evaluate the resistance of soybean germplasm collection against rust diseases. The study wasconducted at Kendalpayak experimental station, Indonesian Legumes and Tuber Crops ResearchInstitute, in June to September 2013. Materials used were 175 genotypes of soybean germplasm collection.Observations of rust disease resistance based on the method of International Working Group on SoybeanRust system. The results showed that out of 175 soybean genotypes tested, 162 genotypes were moderatelyresistant, 12 genotypes were moderately susceptible , and one genotype was susceptible to rust disease.Keywords: soybean , rust disease, resistance.